Soma - Llor, Fernando (Oni Press, 2025)
"Maya is a comic book artist in the middle of a creative crisis. She's constantly stressed about deadlines and feels like she's not doing the type of work she loves. In between trying to fight her writer's block and doling out advice to her best friend on how to finally land a date, Maya receives an unexpected visitor: Soma, an extraterrestrial alien who crashlands in Maya's living room. Soma delivers a message to Maya, warning her that an alien invasion from his own kind is fast approaching, and he needs her help to stop it!"--